Nitrous oxide effluxes from plants as a potentially important source to the atmosphere. Issue 3 (10th October 2018) - Lenhart, Katharina; Behrendt, Thomas; Greiner, Steffen; Steinkamp, Jörg; Well, Reinhard; Giesemann, Anette; Keppler, Frank
Summary: The global budget for nitrous oxide (N2 O), an important greenhouse gas and probably dominant ozone‐depleting substance emitted in the 21 st century, is far from being fully understood. Cycling of N2 O in terrestrial ecosystems has traditionally exclusively focused on gas exchange between the soil surface (nitrification–denitrification processes) and the atmosphere. Terrestrial vegetation has not been considered in the global budget so far, even though plants are known to release N2 O. Here, we report the N2 O emission rates of 32 plant species from 22 different families measured under controlled laboratory conditions. Furthermore, the first isotopocule values (δ 15 N, δ 18 O and δ 15 N sp ) of N2 O emitted from plants were determined. A robust relationship established between N2 O emission and CO2 respiration rates, which did not alter significantly over a broad range of changing environmental conditions, was used to quantify plant‐derived emissions on an ecosystem scale. Stable isotope measurements (δ 15 N, δ 18 O and δ 15 N sp ) of N2 O emitted by plants clearly show that the dual isotopocule fingerprint of plant‐derived N2 O differs from that of currently known microbial or chemical processes. Our work suggests that vegetation is a natural source of N2 O in the environment with a large fraction released by a hitherto unrecognized process.